(untitled) (Comparative & International Education Series, 2021)
Whereas positive effects of internationalisation of higher education (IoHE) have been fairly well identified, both in literature and policies, negative effects are often overlooked. This paper uses the People, Planet, Prosperity (3P) values framework of the United Nations (UN) to map undesired consequences. A Web of Science literature search is used to substantiate these undesired consequences. The results suggest that IoHE includes various types of dilemmas. The 3P framework may inspire HEIs to (re)view their internationalisation activities based on their own particular values framework. Such a review may help HEIs to achieve ethical internationalization by developing an awareness of consequences beyond the own organization and by finding harmony in attending to all its values.